The Psychoeducational Group Uses a Behavioristic Approach with Role Playing in the Tiktok Application to Reduce Student Aggressiveness - Saragih, Nur Afifah Nabila; Firman, Firman; Netrawati, Netrawati (Universitas Trunojoyo Madura, 2023)
Aggressiveness is a form of problem that must be resolved. As a result of the emergence of this aggressiveness will lead to violence and lead to acts of crime. One of the causal factors is because students have not been able to find their own identity so that it can lead to aggressiveness because they cannot stabilize emotionally and cannot control themselves properly. Therefore the need for alleviation of these problems. This study aims to determine the effectiveness of psychoeducational groups using a behavioristic approach with role playing in tiktok to reduce aggressiveness in students. The method used is by using analysis of literature review or literature study. The data used in writing this article was obtained from various literature which includes books, seminar papers or research journals. As for the implementation of this research, it was carried out by collecting theoretical studies regarding the discussion of the problem, then complemented by research relevant to the discussion that will be studied then complicated for more complex conclusions. The results obtained were that the psychoeducational group used a behavioristic approach with role playing in tiktok was effective in reducing student aggressiveness